The Effect of CHOP Chemotherapy Implementation Towards Reduced Global Longitudinal Strain in Non-Hodgkin Lymphoma - Muhammad Perdana Airlanga1, Rochmad Romdoni1, Ami Asharianti2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Doxorubicin in CHOP regimen is still the golden standard of first-line chemotherapy in patients with NHL (Non-Hodgkin Lymphoma); however, it has enormous cardiotoxicity side-effects. Objective: This study aims to investigate the effect of CHOP chemotherapy implementation towards the GLS reduction in cumulative dosage of doxorubicin ? 100 mg/m. Method: This study was pre experimental analysis with modified cohort. The subjects were observed for 1 month, since the first chemotherapy until 1 week after the second chemotherapy. The echocardiogram procedure with ejection fraction and global longitudinal strain was conducted twice which was before the first chemotherapy and 1 week after the second chemotherapy. Results: The implementation of CHOP therapy with the cumulative dosage of ?100 mg/m2 has resulted in reduced GLS from 19.62% to -18.03%. The reduction of GLS>10% was 40% while the LVEF has not been obtained any reduction > 10%. The case of subclinical left ventricular dysfunctions was attained 16%. Conclusion: The implementation of CHOP chemotherapy with the dosage of ?100mg/m2 has been proved to cause reduced GLS and subclinical left ventricular dysfunctions.